Nitrogen depletion blocks growth stimulation driven by the expression of nitric oxide synthase in tobacco - Nejamkin, Andrés (2020)
Fil: Fil: Nejamkin, Andrés. Universidad Nacional de Mar del Plata. Facultad de Ciencias Exactas y Naturales. Instituto de Investigaciones Biológicas; Argentina.